The Prospect of Accountability in Local Governance in Nepal - Dhungana, Hari P. (Journal of Management and Development Studies, 2019)
Government accountability is intrinsic to democracies, as citizens can choose public officials through their popular vote and accordingly exercise some control and oversight over the officials. But elections held in periodic intervals do not allow the scrutiny of the decisions and activities that are conducted on a daily basis. This article examines how to confront this challenge of holding the governments to account, by looking into local governance in Nepal, where citizens have limited knowledge of the government decisions, activities, procedures followed, and their outcomes. This article is developed from the review of policies and laws and semi-structured interviews with elected leaders, civil service personnel, and other stakeholders in select local governments in Nepal. It argues that accountability in local government requires attention not only to laws, but also the practices of civic interaction and the willingness of elected officials and citizens in these engagements. It starts by establishing how the country’s new Constitution of Nepal (2015) espouses a local social contract in view of its division of jurisdictions. It then identifies and analyses the main approaches and tools on government accountability. These encompass broad constitutional provisions to specific legal, institutional and technocratic measures to hold officials to account. It then reveals recent local level experiences around the use of accountability tools and shows that the legacy of widespread collusion and misuse of power continues to be a bottleneck. It concludes that there is a need to foster greater civic demands on accountability and foster measures for deliberation at the municipal level on a more regular basis. Overall, local government accountability should be envisioned as a work-in-progress pursuit and should be coupled with systems of local planning and implementation and vitalization of local democracy.